Novelties in Meriania (Melastomataceae: Merianieae) from Andean rainforests of Colombia - Mendoza-Cifuentes, Humberto; Alvear, Marcela; Almeda, Frank (Phytotaxa, 2014)
Two new species of Meriania (Melastomataceae: Merianieae) are described from the Andean region of Colombia (Northern Andes) in the departments of Caldas, Cauca and Putumayo. Meriania barbosae, known only from one locality in Selva de Florencia National Park, is characterized by its calyptrate flowers, calyptras with obtuse apex, dimorphic stamens and presence of a glandular pubescence on the vegetative organs. Meriania fantastica, from the departments of Cauca and Putumayo, is characterized by its few flowered inflorescences (up to 12 flowers), large flowers (ca. 15 cm in diameter) with bright orange petals and the presence of a scutum at the petiole apex. Both species are Colombian endemics and are only known from a few specimens. Each species is illustrated, compared with presumed relatives, and provided with a conservation assessment using IUCN guidelines.